The Effects of the Marshall Plan Aids to the Development of the Agricultural Sector in Turkey, the 1948-1953 Period - OZER, Mehmet Halis (International Journal of Economics and Financial Issues, 2014)
The purpose of the present study is both to introduce the scope, method and practices of Marshall Aids to Turkey and to analyze their effects on agricultural sector, along with their indirect results for Turkish economy. In this regard, this paper studies how the aids supplied by the Marshall Plan were used in the agricultural sector, to what extent they contributed to the development of the sector and what impacts the contributions had on some macroeconomic values such as the development, per capita income, trade balance and income distribution of Turkey. Of the total 184.5 million dollars supplied between the years 1948 and 1952, 38.282 million was reserved for the agricultural sector. In addition to bringing a high performance to the sector in general, the aids brought about a number of significant contributions such as agricultural mechanization, the farmers’ taking over the modern agricultural production techniques, the enlargement of farmlands and enhancement of agricultural production. Between 1948 and 1953, the economic development relied heavily on the agricultural sector. While the proportion of agricultural sector in gross national product was 38.4% in 1947, it rose to 45% in 1953. On average, Turkish Economy grew by 11% between 1950- 1953 per year. At the same period, thanks to the developments in the agricultural sector, the per capita income increased at a rate of 28%. Keywords: Marshall Aid; Agricultural Sector; Turkish Economy; Economic History JEL Classifications: F5; N4; O1